Gold nanoparticle conjugation enhances the antiacanthamoebic effects of chlorhexidine - Aqeel, Yousuf; Siddiqui, Ruqaiyyah Bano *; Anwar, Ayaz *; Shah, Muhammad Raza; Khan, Naveed Ahmed * (American Society for Microbiology, 2015)
Acanthamoeba keratitis is a serious infection with blinding consequences and often associated with contact lens wear. Early diagnosis, followed by aggressive topical application of drugs, is a prerequisite in successful treatment, but even then prognosis remains poor. Several drugs have shown promise, including chlorhexidine gluconate; however, host cell toxicity at physiologically relevant concentrations remains a challenge. Nanoparticles, subcolloidal structures ranging in size from 10 to 100 nm, are effective drug carriers for enhancing drug potency. The overall aim of the present study was to determine whether conjugation with gold nanoparticles enhances the antiacanthamoebic potential of chlorhexidine. Gold-conjugated chlorhexidine nanoparticles were synthesized. Briefly, gold solution was mixed with chlorhexidine and reduced by adding sodium borohydride, resulting in an intense deep red color, indicative of colloidal gold-conjugated chlorhexidine nanoparticles. The synthesis was con- firmed using UV-visible spectrophotometry that shows a plasmon resonance peak of 500 to 550 nm, indicative of gold nanoparticles. Further characterization using matrix-assisted laser desorption ionization-mass spectrometry showed a goldconjugated chlorhexidine complex at m/z 699 ranging in size from 20 to 100 nm, as determined using atomic force microscopy. To determine the amoebicidal and amoebistatic effects, amoebae were incubated with gold-conjugated chlorhexidine nanoparticles. For controls, amoebae also were incubated with gold and silver nanoparticles alone, chlorhexidine alone, neomycin-conjugated nanoparticles, and neomycin alone. The findings showed that gold-conjugated chlorhexidine nanoparticles exhibited significant amoebicidal and amoebistatic effects at 5 M. Amoebicidal effects were observed by parasite viability testing using a Trypan blue exclusion assay and flow-cytometric analysis using propidium iodide, while amoebistatic effects were observed using growth assays. In contrast, chlorhexidine alone, at a similar concentration, showed limited effects. Notably, neomycin alone or conjugated with nanoparticles did not show amoebicidal or amoebistatic effects. Pretreatment of A. castellanii with goldconjugated chlorhexidine nanoparticles reduced amoeba-mediated host cell cytotoxicity from 90% to 40% at 5 M. In contrast, chlorhexidine alone, at similar concentrations, had no protective effects for the host cells. Similarly, amoebae treated with neomycin alone or neomycin-conjugated nanoparticles showed no protective effects. Overall, these findings suggest that gold-conjugated chlorhexidine nanoparticles hold promise in the improved treatment of A. castellanii keratitis.